Taxonomic review of Ablabesmyia Johannsen (Diptera: Chironomidae: Tanypodinae) from Oriental China, with descriptions of six new species - Niitsuma, Hiromi; Tang, Hongqu (Zootaxa, 2019)
Six new species of the genus Ablabesmyia are described and illustrated from Oriental China: A. (Ablabesmyia) lyrata sp. n. and A. (Ablabesmyia) pectinata sp. n. each based on the male adult and pupa; and A. (Ablabesmyia) huananensis sp. n., A. (Ablabesmyia) praegracilis sp. n., A. (Ablabesmyia) bifurca sp. n. and A. (Karelia) daiensis sp. n. each based on the male adult. The subgenus Karelia is recorded from China for the first time. In addition, A. (Ablabesmyia) alba Chaudhuri, Debnath et Nandi and A. (Ablabesmyia) maculitibialis Chaudhuri, Debnath et Nandi are redescribed based on the male adult, and new distribution records are given for A. (Ablabesmyia) prorasha Kobayashi et Kubota, A. (Ablabesmyia) amamisimplex Sasa and A. (Ablabesmyia) jogancornua Sasa et Okazawa.